SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SOUVENIR PADA HOTEL LESTARI MAKASSAR DENGAN METODE TOPSIS - Helen Loardi; Sudirman; Marlina (STMIK KHARISMA Makassar, 2018)
Souvenir is one of promotional media that used by Hotel Lestari to introduce their product and increase consumer interest. These souvenir should be selected carefully, because each of those has different criteria and value. The criteria that used are price, promotional message suitability, market target reaching area, and souvenir match with target market which become target of promotion. The purpose of this research is to build a Decision Support System that can compare and choose the best souvenirs based on criteria that have been determined by Hotel Lestari. The method used in collecting data process is an interview to Hotel Lestari about the process of selecting souvenirs and doing literature study. The Decision Support System (DSS) calculation method used is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This research build DSS design that can help the Hotel Lestari in determining souvenirs that will be given to the prospective consumers of Hotel Lestari and public. Final decision-making remains in the hands of the hotel's managers, and the system only provides an alternative choice that makes it easy to make decisions.